Perancangan Sistem Informasi Manajemen Aset Kampus Berbasis Web Menggunakan Metode Waterfall - Lut Faizal; Irfan Irfan (Jurnal Ilmiah Sistem Informasi dan Teknik Informatika (JISTI), 2025)
Asset management in higher education institutions plays an important role in supporting the smooth running of academic and administrative activities. The manual system that is still in use causes a number of problems, including the risk of recording errors, data duplication, and delays in inventory reporting. This study aims to develop a web-based campus asset management information system that can improve efficiency, accuracy, and transparency in the inventory process. The system development method uses the Waterfall model with stages of requirements analysis, design, implementation, and testing. The CodeIgniter framework was chosen because it is lightweight, flexible, and supports PHP-based application development structures, while the database uses MySQL. Testing was carried out using the Blackbox Testing method on the main modules, including asset management, asset transfers, inventory reports, user access rights, and dashboards. Testing results showed that all system functions ran according to specifications. The developed system was able to reduce problems in the manual system and provide support for strategic decision-making. Thus, the implementation of a web-based campus asset management information system can be a solution to improve efficiency, accountability, and transparency in asset management in higher education environments.